Disease network data for the pesticide fipronil in rat dopamine cells - Souders Ii, Christopher L; Rushin, Anna; Sanchez, Christina L; Toth, Darby; Adamovsky, Ondrej; Martyniuk, Christopher J (Data in brief, 2021)
Transcriptome data were collected in rat dopamine cells exposed to fipronil for 24 h using microarray analysis. Fipronil is a phenylpyrazole pesticide that acts to inhibit gamma-aminobutyric acid (GABA), blocking inhibitory synaptic transmission in the central nervous system. Transcriptome data were subjected to pathway analysis and subnetwork enrichment analysis. We report that 25 µM fipronil altered transcriptional networks in dopamine-synthesizing cells that are associated with Alzheimer's Disease, Huntington Disease, and Schizophrenia. Data analysis revealed that nerve fibre degeneration, nervous system malformations, neurofibrillary tangles, and neuroinflammation were all disease processes related to the transcriptome profile observed in the rat neuronal cells. Other disease networks altered by fipronil exposure at the transcript level were associated with the mitochondria, including mitochondrial DNA depletion syndrome and mitochondrial encephalomyopathies. These data, along with those presented in Souders et al. (2021), are significant because they increase understanding into the molecular mechanisms underlying human disease following exposures to neuroactive pesticides. These data can be reused to inform adverse outcome pathways for neurotoxic pesticides.
Keywords: Alzheimer's disease; Neurotoxicology; Pesticides; Gene expression; Neurodegeneration; Interactome